Hydraulic Transportation of Highly Thickened Solids in Open Channels - Domínguez, B; Spichiger, A; Jara, R; Pavissich, C (Paste 2009: Proceedings of the Twelfth International Seminar on Paste and Thickened Tailings, 2009)
The increasing shortage and cost of water resources available for the mining industry has brought about a rise in the solid content of hydraulically conveyed slurries, particularly when open channels are used, as is largely the case in countries such as Chile. The applicability restrictions of traditional equations that are based on 50% solids w/w and the limited empirical experience have given raise to test-study research on highly thickened flows. These laboratory tests modelled flows for various solid contents (40%<Sw/w<70%), flume slopes (1.2%<i<3%) and flow rates (50 l/s<Q<100 l/s). Velocity distributions, flow depths, settling limit velocity and rheological flowcharts were obtained, and showed that yield stress and apparent viscosity, as well as solid content, may be represented either in a Bingham or Herschel–Bulkley model. The results indicated a smooth flow without clogging and absence of a settling limit velocity for slurries with over 55% solids. Using Manning’s formula was not validated, because turbulence gradually decreased, as well as dependence on channel roughness. Roughness may be modelled with a coefficient that includes Froude’s number corrected according to the slurry density and volumetric concentration.